1985
DOI: 10.1017/s0022112085001112
|View full text |Cite
|
Sign up to set email alerts
|

Reflections from solitary waves in channels of decreasing depth

Abstract: We have found that the reflected wave that is created by a right-going solitary wave as it travels in a region of slowly changing depth does not satisfy Green's law. The amplitude of the reflected wave is constant along left-going characteristics rather than proportional to the negative fourth root of depth. This new finding allows us to satisfy the mass-flux conservation laws to leading order and establishes that the perturbed Korteweg–de Vries equation is a consistent approximation for the right-going profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
5
19
0
Order By: Relevance
“…Note that, by virtue of the large-radius scaling, the geometric contribution in the cylindrical coordinates first appears in (12), leaving (11) as the classical KdV equation. The various components described by equations (11)- (14) are represented schematically in Fig(2); see the descriptions that follow, where we give a brief outline of what can be deduced at each order.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that, by virtue of the large-radius scaling, the geometric contribution in the cylindrical coordinates first appears in (12), leaving (11) as the classical KdV equation. The various components described by equations (11)- (14) are represented schematically in Fig(2); see the descriptions that follow, where we give a brief outline of what can be deduced at each order.…”
Section: Resultsmentioning
confidence: 99%
“…The propagation of plane solitary waves over variable depth is now well understood ( [3,14,10,11,7]). In this problem it is shown that, starting from an initial solitary-wave solution of the KdV equation ( [12]), the propagation over a region of varying depth introduces a shelf directly behind the primary wave, a left-going (reflected) 'shelf' and another right-going 'shelf' (re-reflection).…”
Section: Introductionmentioning
confidence: 99%
“…Then, returning to the original (dimensionless) variables and coordinates, x, y and t, one may express Eqs. (35) and (36) as follows:…”
Section: A Unperturbed Soliton Solutionsmentioning
confidence: 99%
“…The efforts have then been directed at discovering all the wave components (reflected waves, etc.) which contribute, for example, to the overall mass balance; see [36,30,31,23]. It is a fairly straightforward exercise to analyse the even more general problem of an ambient shear flow which varies as the water flows in a variable-depth environment; the modifications of the classical KdV equation that are evident in equations (4.4) and (4.7) are combined in this new problem; see [25].…”
Section: Extending the Kdv Modelmentioning
confidence: 99%